PENGARUH CUSTOMER RELATIONSHIP MARKETING DAN KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN ANGGOTA PADA KOPERASI CANDRA SEDANA MENGWI BADUNG - Made Agus Adhy Putra; Luh Komang Candra Dewi (Universitas Triatma Mulya, 2022)
The purpose of this study is to determine the influence of customer relationship marketing (X1) and service quality (X2) on the level of member satisfaction (Y) in the candra sedana cooperative mengwi Badung. Where satisfaction is a feeling of pleasure or disappointment for someone who arises after comparing their perceptions or impressions of a product or service and their expectations. One of the factors that influence satisfaction is customer relationship marketing, which is a comprehensive range of strategies and processes to acquire, retain and cooperate with selected consumers to create higher value. In addition to customer relationship marketing, which affects satisfaction, service quality is a company's ability to meet customer needs and desires in accordance with customer expectations. In this study, it is explained that there is a positive effect of customer relationship marketing and service quality on the level of member satisfaction simultaneously. The samples used in this study were 100 respondents. In this study, a statistical analysis was assisted by the SPSS (Statistical for Social Science) 24 computer program for windows. The regression equation obtained is Y = 4.779 + 0.486X1 + 0.181X2. The results of this study indicate that; first, customer relationship marketing has a positive and significant effect on member satisfaction, secondly, service quality has a positive and significant effect on member satisfaction, the third customer relationship marketing and service quality have a simultaneous positive effect of 66.7% on member satisfaction, the four variables of customer relationship marketing have an effect more dominant on the level of member satisfaction. Some suggestions that can be given in this research include; The Candra Sedana Cooperative needs to ask for suggestions and criticism directly from members during the annual membership meeting (RAT) or it can be by making a suggestion box for members. By knowing the wants or needs of members, the cooperative can improve the quality of service so that it can achieve the maximum level of member satisfaction.